THE IMPACT OF INNOVATION AND ENTREPRENEURSHIP EDUCATION AND INITIATIVE PERSONALITY ON ENTREPRENEURIAL INTENTIONS OF HIGHER VOCATIONAL COLLEGE STUDENTS - Qili Zhou; Yudhi Arifani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study focuses on three main issues, namely the relationship between students' general demographic characteristics (e.g., age, gender, place of residence, and annual income) and the entrepreneurial intentions in higher vocational colleges, how innovation and entrepreneurship education influence the entrepreneurial intentions of students in higher vocational colleges, how an active personality shapes the entrepreneurial intentions of students in higher vocational colleges. Employing quantitative research methods and various statistical techniques, including descriptive, correlational, and regression analyses, this paper explores the relationships among demographic variables, innovation and entrepreneurship education, active personality, and entrepreneurial willingness. Based on the findings, several recommendations are presented. The results of this research offer theoretical support for enhancing innovation and entrepreneurship education strategies for students in higher vocational colleges. Students can enhance their entrepreneurial capabilities and boost their self-worth by emphasizing crucial factors such as innovation, entrepreneurship education, and proactive personality traits.